Multi-component transition metal carbide-silicon carbide composite material and preparation method thereof

Through mechanical alloying and SPS sintering technology, a multi-component transition metal carbide-silicon carbide composite material is prepared, which solves the problems of intrinsic brittleness of the material and the negative impact of sintering additives, and realizes high toughness and hardness material preparation, simplifies the process and reduces costs.

CN119736536APending Publication Date: 2025-04-01YANSHAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510037182.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing silicon carbide and transition metal carbide ceramic materials limit their application in high-temperature environments due to their intrinsic brittleness, and traditional sintering additives have a negative impact on the high-temperature oxidation and mechanical properties of the materials.

Method used

Mechanical alloying method is used to mix a variety of transition metal carbide powders with SiC powders, and multi-component transition metal carbide-silicon carbide composite materials are prepared through SPS sintering technology. Ti powder is used to modify metal carbide powders to reduce the sintering temperature and improve the fracture toughness and hardness of the material.

Benefits of technology

The preparation of multi-component transition metal carbide-silicon carbide composites with high density and excellent performance at lower sintering temperatures is achieved, which simplifies the process flow and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736536A_ABST
    Figure CN119736536A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-component transition metal carbide and SiC combined composite material and a preparation method thereof. The sintering powder is prepared from raw materials, so that the sintering temperature is reduced, and sintering is promoted. The novel multi-component transition metal carbide and SiC combined composite material is prepared from the following raw materials: Ti powder, TiC powder, ZrC powder, HfC powder, VC powder, NbC powder, TaC powder, Mo2C powder, WC powder and SiC powder. During preparation, the raw materials are mixed in a planetary ball mill according to the proportion of different carbides; after uniformly mixing, filling a hard alloy mold with the mixture for pre-pressing; and then, carrying out spark plasma sintering (SPS) on the pre-pressed sample. And then cooling and pressure relief are conducted, and the multi-component transition metal carbide and SiC combined composite material is prepared. According to the method, sintering is promoted through vacancies in a system, the hardness and fracture toughness of the multi-component transition metal carbide and SiC combined composite material are improved, the process is simplified through the one-step powder preparation mode, and the preparation period is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a multi-component transition metal carbide-silicon carbide composite material and a preparation method thereof. Background Art

[0002] Silicon carbide ceramics have excellent properties such as high temperature strength, strong oxidation resistance, good wear resistance, good thermal stability, high thermal conductivity, high hardness, and resistance to thermal shock and chemical corrosion [Jiang Dongliang, Kuang Gao, Pan Zhensu, et al. Oxidation behavior and high temperature strength of hot-pressed silicon carbide with different additives [J]. Journal of Inorganic Materials, 1988(1):49-55]. Therefore, silicon carbide ceramics have been widely used as various corrosion-resistant containers and pipelines in the petrochemical industry; they have been successfully used as various bearings, cutting tools and mechanical sealing components in the machinery industry; and they are also considered to be the most promising candidate materials for the future manufacture of gas turbines, rocket nozzles and engines in the aerospace and automotive industries [Wang Ming, Dong Zhiguo, Zhang Xiaoyue, et al. Application of continuous fiber reinforced silicon carbide ceramic matrix composites in aeroengines [J]. Aviation Manufacturing Technology, 2014,450(6):10-13].

[0003] Zhang Yong et al. used silicon carbide powder with Al2O3 and Y2O3 sintering aids as raw materials, and quickly prepared silicon carbide ceramics through spark plasma sintering (SPS) technology, analyzed the material densification process, and focused on studying the influence of sintering process parameters on material density and mechanical properties. The results show that when the sintering temperature and pressure of the SPS process parameters are 1600 ℃ and 50 MPa, respectively, after 5 minutes of sintering, the density of silicon carbide ceramics can reach 99.1%, the hardness is HV2550, and the fracture toughness is 8.34 MPa.m 1 / 2 , the bending strength reaches 684 MPa. However, this traditional sintering aid has a significant negative impact on the high-temperature oxidation resistance and high-temperature mechanical properties of the material [Zhang Yong, He Xinbo, Qu Xuanhui, et al. Preparation of dense silicon carbide ceramics by spark plasma sintering process [J]. Mechanical Engineering Materials, 2008, 32(3):45-47].

[0004] Transition metal carbides have excellent properties such as high melting point (>2800℃), high hardness (20-25GPa), low friction coefficient, high electrical and thermal conductivity, strong corrosion resistance and wear resistance, and have become important industrial materials for application and research. Single-component carbides such as TiC and WC are often prepared as cemented carbides for use in mechanical processing and other fields, while ZrC, HfC and TaC are often used in high-temperature structural fields [Liu Dongliang, Jin Yongzhong, Deng Jianguo. Oxidation resistance of ultra-high temperature ceramic materials [J]. Journal of Ceramics, 2010, 31(01): 151-157]. However, their inherent intrinsic brittleness severely limits the use of various single-component carbide ceramics. Therefore, two-component composites, three-component composites and complex composite materials with more components have been continuously studied and prepared from theoretical calculations and experiments to adjust the toughness of the materials. The solid solution strengthening between the components has played a great role in improving the performance of the materials [Xu Liang, Wang Hongjie, Su Lei. Research Progress of High Entropy Ceramics [J]. Aerospace Materials and Processes, 2021,1: 1-9]. Luo Y et al. used face-centered cubic SiC and spark plasma sintering to prepare TiC-SiC composite materials with a density of 98% and high strength and toughness. When the mass fraction of TiC is 30%, its hardness reaches 28GPa and its toughness is about 6.4 MPa.m1 / 2. However, the cubic silicon carbide used in it has not yet been industrialized and mass-produced, and the cost is relatively high [Luo Y, Li S, Pan W, et al. Fabrication and mechanical evaluation of SiC–TiC nanocomposites by SPS [J]. Materials Letters, 2004, 58(1):150-153].

[0005] In order to improve the intrinsic brittleness of silicon carbide and transition metal carbides, the present invention adopts a mechanical alloying method to mix Ti powder, TiC powder, ZrC powder, HfC powder, VC powder, NbC powder, TaC powder, Mo2C powder, WC powder and SiC powder, adopts SPS sintering technology to prepare a composite material of multi-component transition metal carbide combined with SiC, and uses Ti powder to modify the metal carbide powder, so as to utilize the vacancies in the system to reduce the sintering temperature and promote sintering, thereby improving the fracture toughness, hardness, corrosion resistance and other properties of the composite material, and at the same time simplifies the process and reduces the production cost of the composite material. Summary of the invention

[0006] The present invention adopts a one-step method to prepare a composite material of multi-component transition metal carbide combined with SiC, simplifies the preparation process, and based on the existence of vacancies in the system, can increase the configuration entropy of the system, thereby reducing the sintering temperature and promoting sintering. The novel composite material of multi-component transition metal carbide combined with SiC is prepared by Ti powder, TiC powder, ZrC powder, HfC powder, VC powder, NbC powder, TaC powder, Mo2C powder, WC powder, and SiC powder raw materials. The following four composite materials were prepared using the above powders: (1) The volume percentages of the chemical components of the Ti / TiC / ZrC / VC / NbC / SiC composite material are as follows: Ti powder 11 vol.%, TiC powder 12 vol.%, ZrC powder 15 vol.%, VC powder 11 vol.%, NbC powder 13 vol.%, SiC powder 37 vol.%; (2) The volume percentages of the chemical components of the Ti / TiC / ZrC / HfC / VC / NbC / TaC / SiC composite material are as follows: Ti powder 8 vol.%, TiC powder 9 vol.%, ZrC powder 12 vol.%, HfC powder 12 vol.%, VC powder 9 vol.%, NbC powder 10 vol.%, TaC powder 11 vol.%, SiC powder 29 vol.%; (3) The volume percentages of the chemical components of the Ti / TiC / ZrC / VC / NbC / Mo2C / WC / SiC composite material are as follows: Ti powder 9 vol.%, TiC powder 10 vol.%, ZrC powder 12 vol.%, VC powder 9 vol.%, NbC powder 11 vol.%, Mo2C powder 9 vol.%, WC powder 10 vol.%, SiC powder 30 vol.%; (4) The volume percentages of the chemical components of the Ti / TiC / ZrC / HfC / VC / NbC / TaC / Mo2C / WC / SiC composite material are as follows: Ti powder 7 vol.%, TiC powder 8 vol.%, ZrC powder 10 vol.%, HfC powder 10 vol.%, VC powder 9 vol.%, NbC powder 10 vol.%, TaC powder 11 vol.%, Mo2C powder 7 vol.%, WC powder 8 vol.%, SiC powder 25 vol.%.

[0007] The purity of Ti powder is 99.5%, and the particle size is 1-2 μm; the purity of TiC powder is 99.5%, and the particle size is 3 μm; the purity of ZrC powder is 99.5%, and the particle size is 1-3 μm; the purity of VC powder is 99.5%, and the particle size is 1-3 μm; the purity of NbC powder is 99.5%, and the particle size is 1-3 μm; the purity of HfC powder is 99.5%, and the particle size is 1-3 μm; the purity of TaC powder is 99.5%, and the particle size is 3 μm; the purity of Mo2C powder is 99.5%, and the particle size is 1-3 μm; the purity of WC powder is 99.5%, and the particle size is 3 μm; the purity of SiC powder is 99.5%, and the particle size is 1 μm.

[0008] The present invention also discloses a method for preparing a multi-component transition metal carbide-silicon carbide composite material, comprising the following steps: S1. After adding dispersant to the raw material powders of each preset mass fraction, the powders were placed in a WC carbide ball mill for ball milling. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling was performed for 20 hours, each rotation was 30 minutes, and the machine was stopped for 30 minutes for heat dissipation to obtain a mixed powder; S2. Pre-press the mixed powder prepared in step S1 at a pre-pressing pressure of 500 MPa for 60 s; then, perform spark plasma sintering (SPS) on the pre-pressed sample at a sintering pressure of 40 MPa, a sintering temperature of 1900°C, and a holding time of 10 min; then, cool and release the pressure to obtain a multi-component transition metal carbide-silicon carbide composite material.

[0009] Furthermore, the dispersant is industrial ethanol with a purity of ≥99.7%, and 0.2-0.5 mL of the dispersant is added to every 10 g of powder.

[0010] Furthermore, the specific sintering process and parameters in step S2 are as follows: first, slowly apply pressure to the sample to 40MPa; then, heat from room temperature to 600℃ at a heating rate of 100℃ / min, and keep at 600℃ for 5 minutes; then heat from 600℃ to 1900℃ at a heating rate of 100℃ / min, and keep at the terminal temperature for 10 minutes. Cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a novel multi-component transition metal carbide combined with SiC composite material The main purpose of the present invention is to provide a high-toughness multi-component transition metal carbide combined with SiC composite material powder and sintered body material, which can obtain a composite material with good density and excellent performance under a simpler process and a lower sintering temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0012] Figure 1 is the XRD diagram of the Ti / TiC / ZrC / VC / NbC / SiC composite material in Example 1, Figure 2 Surface SEM image of the Ti / TiC / ZrC / VC / NbC / SiC composite material in Example 1; Figure 3 is the XRD diagram of the Ti / TiC / ZrC / HfC / VC / NbC / TaC / SiC composite material in Example 2, Figure 4 Surface SEM image of the Ti / TiC / ZrC / HfC / VC / NbC / TaC / SiC composite material in Example 2; Figure 5 is the XRD diagram of the Ti / TiC / ZrC / VC / NbC / Mo2C / WC / SiC composite material in Example 3, Figure 6 Surface SEM image of the Ti / TiC / ZrC / VC / NbC / Mo2C / WC / SiC composite material in Example 3; Figure 7 is the XRD diagram of the Ti / TiC / ZrC / HfC / VC / NbC / TaC / Mo2C / WC / SiC composite material in Example 4, Figure 8 This is the surface SEM image of the Ti / TiC / ZrC / HfC / VC / NbC / TaC / Mo2C / WC / SiC composite material in Example 4. DETAILED DESCRIPTION

[0013] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0014] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0016] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values ​​of the parts and steps described in these embodiments do not limit the scope of the present invention. At the same time, it should be clear that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.

[0017] The detection equipment described in the present invention are all instruments used in conventional detection means, such as X-ray diffractometer, hardness tester, scanning electron microscope, etc.

[0018] Exemplary embodiments, features and performance aspects of the present invention will be described in detail below.

[0019] The raw material powders of each preset mass fraction composition were added with dispersant and then placed in a WC carbide ball mill for ball milling. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling was performed for 20 hours, each rotation was 60 minutes, and the machine was stopped for 30 minutes for heat dissipation to obtain a mixed powder. The prepared mixed powder was pre-pressed with a pre-pressing pressure of 500 MPa and a pre-pressing time of 60 seconds. Then, the pre-pressed sample was subjected to SPS sintering with a sintering pressure of 40 MPa, a sintering temperature of 1700-1900 °C, and a holding time of 10 minutes. Then, the temperature was lowered and the pressure was released to obtain a sintered composite material of multi-component transition metal carbides combined with SiC.

[0020] Example 1 The raw material formula is weighed according to the following mass percentages:

[0021] S1. Add dispersant to the raw material powder composed of the mass fraction in Table 1 and put it into a WC hard alloy ball mill for ball milling. The ball-to-material mass ratio is 20:1, the rotation speed is 450 r / min, and the ball milling is carried out for 20 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1, the pre-pressing pressure is 500 MPa, and the pre-pressing time is 60 s. Then, the pre-pressed sample is subjected to SPS sintering, the sintering pressure is 40 MPa, and the heating system is as follows: first, the temperature is increased from room temperature to 600 ℃ at a heating rate of 100 ℃ / min, and kept at 600 ℃ for 5 min; then the temperature is increased from 600 ℃ to 1900 ℃ at a heating rate of 100 ℃ / min, and kept at 10 min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a Ti / TiC / ZrC / VC / NbC / SiC composite material. The sintered Ti / TiC / ZrC / VC / NbC / SiC composite material sample is ground and polished, and then the microstructure and performance are tested and analyzed. The results show that the density is 97.4%, the hardness is 19.25 GPa, and the fracture toughness is 8.05 MPa·m 1 / 2 . Example 2

[0022] The raw material formula is weighed according to the following mass percentages:

[0023] S1. Add dispersant to the raw material powder composed of the mass fraction in Table 2, and then put it into a WC hard alloy ball mill for ball milling. The ball-to-material mass ratio is 20:1, the speed is 450 r / min, and the ball milling is carried out for 20 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1, the pre-pressing pressure is 500 MPa, and the pre-pressing time is 60 s. Then, the pre-pressed sample is subjected to SPS sintering, the sintering pressure is 40 MPa, and the heating system is as follows: first, the temperature is increased from room temperature to 600 °C at a heating rate of 100 °C / min, and kept at 600 °C for 5 min; then the temperature is increased from 600 °C to 1900 °C at a heating rate of 100 °C / min, and kept at 10 min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a Ti / TiC / ZrC / HfC / VC / NbC / TaC / SiC composite material. The sintered Ti / TiC / ZrC / HfC / VC / NbC / TaC / SiC composite material samples were polished and then analyzed for microstructure and performance. The results showed that the density was 98.5%, the hardness was 20.41 GPa, and the fracture toughness was 8.07 MPa·m 1 / 2 .

[0024] Example 3 The raw material formula is weighed according to the following mass percentages:

[0025] S1. Add dispersant to the raw material powders composed of the mass fractions in Table 3 and put them into a WC carbide ball mill for ball milling. The ball-to-material mass ratio is 20:1, the rotation speed is 450 r / min, and the ball milling is carried out for 10 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1 at a pre-pressing pressure of 500 MPa and a pre-pressing time of 60 s. Then, the pre-pressed sample is subjected to SPS sintering at a sintering pressure of 40 MPa. The heating system is as follows: first, the temperature is increased from room temperature to 600 °C at a heating rate of 100 °C / min, and kept at 600 °C for 5 min; then, the temperature is increased from 600 °C to 1900 °C at a heating rate of 100 °C / min, and kept at 10 min. The mixture is cooled in the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a Ti / TiC / ZrC / VC / NbC / Mo2C / WC / SiC composite material. The sintered Ti / TiC / ZrC / VC / NbC / Mo2C / WC / SiC composite material samples were polished and then analyzed for microstructure and performance. The results showed that the density was 99.7%, the hardness was 19.81 GPa, and the fracture toughness was 7.45 MPa·m 1 / 2 .

[0026] Example 4 The raw material formula is weighed according to the following mass percentages:

[0027] S1. Add dispersant to the raw material powders composed of the mass fractions in Table 3 and put them into a WC carbide ball mill for ball milling. The ball-to-material mass ratio is 20:1, the rotation speed is 450 r / min, and the ball milling is carried out for 10 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1, the pre-pressing pressure is 500 MPa, and the pre-pressing time is 60 s. Then, the pre-pressed sample is subjected to SPS sintering, the sintering pressure is 40 MPa, and the heating system is as follows: first, the temperature is increased from room temperature to 600 °C at a heating rate of 100 °C / min, and kept at 600 °C for 5 min; then the temperature is increased from 600 °C to 1900 °C at a heating rate of 100 °C / min, and kept at 10 min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a Ti / TiC / ZrC / HfC / VC / NbC / TaC / Mo2C / WC / SiC composite material. The sintered Ti / TiC / ZrC / HfC / VC / NbC / TaC / Mo2C / WC / SiC composite material samples were polished and then analyzed for microstructure and performance. The results showed that the density was 93.7%, the hardness was 19.25 GPa, and the fracture toughness was 7.20 MPa·m 1 / 2 .

[0028] The results of the above examples are analyzed, and it is found that the composite material with a raw material sintering temperature of 1900° C. has the best comprehensive performance. The present invention can prepare a composite material with excellent performance through a simple preparation method.

[0029] The present invention is described above by way of example, but the present invention is not limited to the details of the above embodiments, and the present invention can be implemented in other specific forms without departing from the basic features of the present invention. Any changes or modifications made based on the present invention belong to the scope of protection claimed by the present invention.

Claims

1. A multi-component transition metal carbide-silicon carbide composite material, characterized in that: The multi-component transition metal carbide combined with SiC composite material powder is prepared by using a variety of raw materials selected from Ti powder, TiC powder, ZrC powder, HfC powder, VC powder, NbC powder, TaC powder, Mo2C powder, WC powder and SiC powder.

2. The multi-component transition metal carbide-silicon carbide composite material according to claim 1, characterized in that: The above powders were used to prepare a Ti / TiC / ZrC / VC / NbC / SiC composite material, and the volume percentages of its chemical components were as follows: Ti powder 11 vol.%, TiC powder 12 vol.%, ZrC powder 15 vol.%, VC powder 11 vol.%, NbC powder 13 vol.%, and SiC powder 37 vol.%.

3. The multi-component transition metal carbide-silicon carbide composite material according to claim 1, characterized in that: The above powders were used to prepare a Ti / TiC / ZrC / HfC / VC / NbC / TaC / SiC composite material, and the volume percentages of its chemical components were as follows: Ti powder 8 vol.%, TiC powder 9 vol.%, ZrC powder 12 vol.%, HfC powder 12 vol.%, VC powder 9 vol.%, NbC powder 10 vol.%, TaC powder 11 vol.%, and SiC powder 29 vol.%.

4. The multi-component transition metal carbide-silicon carbide composite material according to claim 1, characterized in that: The above powders were used to prepare Ti / TiC / ZrC / VC / NbC / Mo2C / WC / SiC composite materials, and the volume percentages of the chemical components were as follows: Ti powder 9 vol.%, TiC powder 10 vol.%, ZrC powder 12 vol.%, VC powder 9 vol.%, NbC powder 11 vol.%, Mo2C powder 9 vol.%, WC powder 10 vol.%, and SiC powder 30 vol.%.

5. The multi-component transition metal carbide-silicon carbide composite material according to claim 1, characterized in that: The above powders were used to prepare a Ti / TiC / ZrC / HfC / VC / NbC / TaC / Mo2C / WC / SiC composite material, whose chemical components by volume percentage were as follows: Ti powder 7 vol.%, TiC powder 8 vol.%, ZrC powder 10 vol.%, HfC powder 10 vol.%, VC powder 9 vol.%, NbC powder 10 vol.%, TaC powder 11 vol.%, Mo2C powder 7 vol.%, WC powder 8 vol.%, SiC powder 25 vol.%.

6. The multi-component transition metal carbide-silicon carbide composite material according to claim 1, characterized in that: The purity of the Ti powder is 99.5%, and the particle size is 1-2 μm; the purity of the TiC powder is 99.5%, and the particle size is 3 μm; the purity of the ZrC powder is 99.5%, and the particle size is 1-3 μm; the purity of the VC powder is 99.5%, and the particle size is 1-3 μm; the purity of the NbC powder is 99.5%, and the particle size is 1-3 μm; the purity of the HfC powder is 99.5%, and the particle size is 1-3 μm; the purity of the TaC powder is 99.5%, and the particle size is 3 μm; the purity of the Mo2C powder is 99.5%, and the particle size is 1-3 μm; the purity of the WC powder is 99.5%, and the particle size is 3 μm; the purity of the SiC powder is 99.5%, and the particle size is 1 μm.

7. A method for preparing the multi-component transition metal carbide-silicon carbide composite material as claimed in claim 1, characterized in that: The following steps are involved: S1. After adding dispersant to the raw material powders of each preset mass fraction, the powders were placed in a WC carbide ball mill for ball milling. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling was performed for 20 hours, each rotation was 30 minutes, and the machine was stopped for 30 minutes for heat dissipation to obtain a mixed powder; S2. Pre-press the mixed powder prepared in step S1 at a pre-pressing pressure of 500 MPa for 60 s; then, perform spark plasma sintering (SPS) on the pre-pressed sample at a sintering pressure of 40 MPa, a sintering temperature of 1900°C, and a holding time of 10 min; then, cool and release the pressure to obtain a multi-component transition metal carbide-silicon carbide composite material.

8. The method for preparing the multi-component transition metal carbide-silicon carbide composite material according to claim 7, characterized in that: The dispersant is industrial ethanol with a purity of ≥99.7%, and 0.2-0.5 mL of the dispersant is added to every 10 g of powder.

9. The method for preparing the multi-component transition metal carbide-silicon carbide composite material according to claim 7, characterized in that: The specific sintering process and parameters in step S2 are as follows: first, slowly apply pressure to the sample to 40 MPa; then, heat from room temperature to 600 °C at a heating rate of 100 °C / min, and keep at 600 °C for 5 min; then heat from 600 °C to 1900 °C at a heating rate of 100 °C / min, and keep at the terminal temperature for 10 min. Cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a novel multi-component transition metal carbide combined with SiC composite material.

Citation Information

Cited By

  • MAX-transition metal carbide / nitride / boride composite material and preparation method thereof

    CN121627410A